2018
DOI: 10.15237/gida.gd18076
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Content, Antioxidant and Antidiabetic Potentials of Seven Edible Leaves

Abstract: The objectives of this study were to investigate antioxidant and enzyme inhibitory activity of ethanolic and aqueous extracts of seven leaves. The antioxidant activity of the leaves was determined by two different methods: DPPH and β-carotene-bleaching test (βC). The enzyme inhibitory activity was evaluated against α-glucosidase. Antioxidant (EC50) and α-glucosidase (IC50) activity were determined as 8.29-238.8 g of leaf/g of DPPH and 35.59-620.29 μg/mL respectively. Among seven leaves studied, leaf of grape (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…For the mixture 0.4 mL of diluted extract solution was used to mix with 2 mL of Folin-Ciocalteu reagent (the reagent was pre-diluted by distilled water 10 times ) and 1.6 mL of sodium carbonate (7.5% w /v). At room temperature after 60 minutes of incubation, the absorbance was measured at 765 nm against the blank solution prepared using a UV-Visspectrophotometer (Akyurt et al, 2018).Our findings in our study evaluated as mg GAE/kg.…”
Section: Methodsmentioning
confidence: 88%
“…For the mixture 0.4 mL of diluted extract solution was used to mix with 2 mL of Folin-Ciocalteu reagent (the reagent was pre-diluted by distilled water 10 times ) and 1.6 mL of sodium carbonate (7.5% w /v). At room temperature after 60 minutes of incubation, the absorbance was measured at 765 nm against the blank solution prepared using a UV-Visspectrophotometer (Akyurt et al, 2018).Our findings in our study evaluated as mg GAE/kg.…”
Section: Methodsmentioning
confidence: 88%
“…Regarding the previous study by Mehdi 55 and groups agree with our results, they are estimated that the Iranian Utica dioica L. leaves for pre and post flowering steps; water had higher inhibition than ether extract. Similarly, Bashyigit et al, 56 results showed the hydroalcoholic extract of nettle exhibited high value ability of antioxidants. Other groups assessed that the higher concentration of phenolic compounds in 80% ethanol extract was associated with the highest antioxidant activity in beta-carotene bleaching method 57 .…”
mentioning
confidence: 76%
“…The polyphenol content of quince leaves was higher than that of tea, making them a safe and inexpensive alternative to conventional treatment. Akyurt et al [101] compared the ability of leaf extracts of C. oblonga and six other species: V. vinifera, Morus alba, Phaseolus vulgaris, Prunus avium, Urtica dioica, and Beta vulgaris, to inhibit α-glucosidase activity. Of the examined leaves, the leaves of V. vinifera, C. oblonga, and Urtica dioica showed the strongest inhibition of α-glucosidase.…”
Section: Antidiabetic Properties Of Leaves (Figure 10b)mentioning
confidence: 99%